Knowledge, Attitude and their Effect on the Recently Graduated Employees’ Financial Management Practices and Satisfaction - Subarna Bir, JBR (Economic Literature, 2016)
Researches on financial management practices still seems to be in its embryonic stage, particularly in the context of Nepal where studies taking Nepalese sample are in trivial number though this issue has received an increased attention internationally. This study carries in its womb the objectives of determining the effect of financial knowledge and attitude on the financial management practices and satisfaction with the financial status by taking a total of 110 recently graduated employees as sample respondent. The Family Resource management model originally conceptualized by Deacon and Firebaugh (1988)has been the inspiration for the conceptual framework so constructed for this study. The more positive financial attitudes, longer the job experience and stronger the family’s financial background, the better was the financial management practices among the recently graduated employees. Likewise, wealthy financial background of the respondent’s family, their longer job experience and sound financial management practices adopted by them were related to higher satisfaction with financial status. However, financial knowledge possessed by them was found to be insignificant in predicting their financial management practices as well as satisfaction with their financial status. Economic Literature Vol.12 2014: 69-81